A Study on the impact of Coping Strategies over Stress Management – An Empirical Study - et. al., Ch.Narahari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present study we analyze the employees’ perception towards coping measures adopted byfirms in software industry. The considered coping constructs adopted for the study in stress abatement areVenting of Emotions,Problem Focused, Seeking Information and emotional support, Positive Emotion-Focused, were, employee perception was acquired by a systematic survey.A total sample of 800 employees’perceptions have been collected through simple random technique and out of which survey respondents, irregular responses are eliminated finally 756 samples are determined for statistical analysis. Chi-square test was performed to determine the association between perceptions and model constructs. Results are reported and discussions are made as per the results and in correlation between results of previous literature.Finally, suggestions and future indication for extension of the study are proposed.